2020
DOI: 10.1007/978-981-15-6627-1_10
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Amplitude Modulations in Speech to Perceived Charisma

Abstract: Speech contains pronounced amplitude modulations in the 1-9 Hz range, correlating with the syllabic rate of speech. Recent models of speech perception propose that this rhythmic nature of speech is central to speech recognition and has beneficial effects on language processing. Here, we investigated the contribution of amplitude modulations to the subjective impression listeners have of public speakers. The speech from US presidential candidates Hillary Clinton and Donald Trump in the three TV debates of 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…114 The ENV-Om coherence as a physical realization of the rhythmic frame may become a very useful tool to predict the comprehensibility of an utterance from the angle of rhythmicity, and at least partially explain why, given the same signal condition, listeners prefer some utterances to others. 115 From the linguistic perspective, the existence of speech rhythm has been debated because of (a)…”
Section: Discussionmentioning
confidence: 99%
“…114 The ENV-Om coherence as a physical realization of the rhythmic frame may become a very useful tool to predict the comprehensibility of an utterance from the angle of rhythmicity, and at least partially explain why, given the same signal condition, listeners prefer some utterances to others. 115 From the linguistic perspective, the existence of speech rhythm has been debated because of (a)…”
Section: Discussionmentioning
confidence: 99%
“…Results by Weiss et al (2021b) confirmed the same from the standpoint of voice likability: variability of fundamental frequency (pitch) turned out to be a dominating correlate of likable voices in male and female speakers. Listeners also tend to find more rhythmic speech to be more likable, as Bosker (2021) has shown based on research on fluctuations in amplitude.…”
Section: Introductionmentioning
confidence: 90%
“…Specifically for English, which is the focus of this investigation, acoustic and perceptual studies of temporal and spectral aspects of charismatic delivery show that louder rather than quieter speech is associated with charisma [19]; or better yet, it is loudness 1 variability that recipients associate with charisma [23,24] or being a "good speaker" [25] and that make the most charismatic public speakers like Steve Jobs, the founder of Apple, stand out [26], while others, like Elon Musk, call themselves "a bad public speaker" [27].…”
Section: The Phonetics Of Charismamentioning
confidence: 97%